2019
DOI: 10.3389/fonc.2019.00763
|View full text |Cite
|
Sign up to set email alerts
|

Is Adjuvant Chemotherapy Worthwhile After Radical Resection for Single Lung Metastasis From Colorectal Cancer? A Multicentric Analysis Evaluating the Risk of Recurrence

Abstract: Background: Adjuvant chemotherapy after resection of colorectal cancer (CRC) lung metastases may reduce recurrences and improve survival. The choice of best candidates for adjuvant chemotherapy in this setting is controversial, especially when a single lung metastases (SLM) is resected. The aim of this study is to evaluate the risk of recurrence after radical resection for single lung metastasis from CRC. Patients and methods: Demographic, clinical, and pathological data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Second, the DFI was a prognostic factor in some previous studies. 5 , 26 In this study, we calculated the DFIs using three kinds of method to explore the influence of calculation method. As a result, none of the DFIs was identified as prognostic factor in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the DFI was a prognostic factor in some previous studies. 5 , 26 In this study, we calculated the DFIs using three kinds of method to explore the influence of calculation method. As a result, none of the DFIs was identified as prognostic factor in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding DFI, Yokoyama et al 37 identified short DFI (<24 mo) and N2 of the primary lesion as risk factors for recurrence after pulmonary resection, but not for survival. Other reports have similarly identified DFI as a risk of recurrence; however, a cutoff for DFI was reported as 36 mo by Davini et al, 31 while it was determined to be 12 mo by Rapicetta et al 32 It is a convincing theory that DFI is a predictor of prognosis, as shorter DFI are expected to be biologically more malignant. However, the cutoff period has not yet been established because there is a great deal of variability in the optimal period.…”
Section: Surgical Treatmentmentioning
confidence: 98%
“…Table 1 shows the major recent reports investigating the long‐term survival of patients who underwent pulmonary resection and those who did not. 28 , 30 , 31 , 32 , 33 Although the 5‐y overall survival rate of pulmonary resection tends to be better in retrospective studies, the survival rate of nonsurgery is also worthy of comparison.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Patients who were most likely to benefit most from systemic chemotherapy were those with high value of preoperative CEA, hypermetabolism on the PET CT scan, previous extra-thoracic resected metastasis, and short (<12 months) DFI, all of which were features associated with increased risks of disease recurrence (68).…”
Section: Chemotherapy In Patient With Pulmonary Metastasectomymentioning
confidence: 99%